2013
DOI: 10.1002/pc.22561
|View full text |Cite
|
Sign up to set email alerts
|

Nonwoven polylactic acid and flax biocomposites

Abstract: Flax fiber-reinforced polylactic acid (PLA) biocomposites were made using a new technique incorporating an air-laying nonwoven process. Flax and PLA fibers were blended and converted to fiber webs in the airlaying process. Composite prepregs were then made from the fiber webs. The prepregs were finally converted to composites by compression molding. The relationship between the main process variables and the properties of the biocomposite was investigated. It was found that with increasing flax content, the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 26 publications
1
38
1
Order By: Relevance
“…It can be seen that the voids of the 3D biocomposites increased as the nominal fiber fraction by weight increased. In the previous paper , SEM micrographs indicated that the addition of flax fiber resulted in the presence of voids. The voids are closely related to the processing conditions, because they can be formed by gases which may be generated in the thermal process.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…It can be seen that the voids of the 3D biocomposites increased as the nominal fiber fraction by weight increased. In the previous paper , SEM micrographs indicated that the addition of flax fiber resulted in the presence of voids. The voids are closely related to the processing conditions, because they can be formed by gases which may be generated in the thermal process.…”
Section: Resultsmentioning
confidence: 88%
“…The nonwoven webs are thermally consolidated before finally converted to biocomposites. The nonwoven web is converted into biocomposites by the compression molding and hot‐pressing process . The crushing test was used to evaluate the mechanical properties of 3D biocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the higher void content of the fiber reinforced composites, in particular, the random mat composites may have a role in accelerating water absorption. In this way, water/moisture initiates the biodegradation process of flax/PLA laminate [30]. Water absorbency is expressed in terms of mass percentage gain of the composites.…”
Section: Resultsmentioning
confidence: 99%
“…Nonwoven webs (250 g/m 2 ) were prepared from flax/PLA blends using a mass ratio of 50:50 (wt.%) by means of an air laying process [30]. An air laying web forming machine generally consists of feeding, carding, stripping, transporting and condensing units which ensures the isotropic fiber orientation distribution, leading to isotropic composites.…”
Section: Randomly Aligned Flax Fiber Preformsmentioning
confidence: 99%
“…For instance, previous researches [24] demonstrated that flax fibres start to slowly degrade between 200 ˚C and 220 ˚C. Above this temperature, the degradation of fibres is irreversible which sets a limit excluding the possibility of using thermoplastic polymers with a melting point higher than this value [23].…”
Section: Introductionmentioning
confidence: 99%